Unveiling the Role of OCB and Work Engagement in Driving Performance in Socio-Religious Organizations: A Systematic Literature Review - Ahmad Alyani Addarain; Gumgum Gumelar Fajar Rakhman; Yufiarti Yufiarti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This Systematic Literature Review (SLR) examines the relationship between Organizational Citizenship Behavior (OCB) and Work Engagement (WE) in the context of socio-religious organizations. OCB refers to voluntary behaviors that support the effectiveness of the organization, while WE is a positive psychological state that reflects the commitment and energy of employees to their work. By analyzing research conducted in the last decade, this review outlines findings related to the influence of these two concepts on organizational performance, particularly in faith-based social organizations. This SLR highlights the contribution of the OCB and WE dimensions in strengthening citizenship engagement and behavior in the context of socio-religious organizations.